2017
DOI: 10.1136/bmjopen-2016-013443
|View full text |Cite
|
Sign up to set email alerts
|

Referral pathways for patients with TIA avoiding hospital admission: a scoping review

Abstract: ObjectiveTo identify the features and effects of a pathway for emergency assessment and referral of patients with suspected transient ischaemic attack (TIA) in order to avoid admission to hospital.DesignScoping review.Data sourcesPubMed, CINAHL Web of Science, Scopus.Study selectionReports of primary research on referral of patients with suspected TIA directly to specialist outpatient services.Data extractionWe screened studies for eligibility and extracted data from relevant studies. Data were analysed to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Two types of medical referral can be distinguished:( 10 ). The first type is Office Based Physician (OBP) referral: The first TIA clinics created in Paris and Oxford were dedicated to accommodating primary care physicians (PCP) to refer TIA patients via a toll free number ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of medical referral can be distinguished:( 10 ). The first type is Office Based Physician (OBP) referral: The first TIA clinics created in Paris and Oxford were dedicated to accommodating primary care physicians (PCP) to refer TIA patients via a toll free number ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that high ABCD score indicates high incidence of stroke within 30 d. ABCD score reached 0-2, 3, 4, 5, and 6 with risks of stroke reaching 0%, 3.5%, 7.6%, 21.3% and 31.3% respectively; at the same time, ABCD score of 5-6 points within 30 d stroke risk is eight times higher than that of ABCD score of 4 points or less. 8,9 The study suggests good clinical use of this score to predict reliability of the risk of stroke after TIA. ABCD score can identify high risk of stroke patients at an early period.…”
Section: Abcd Scorementioning
confidence: 99%
“…2,8,9,11,22 In 2010, researchers established ABCD3 and ABCD3I score. 15 Which on the basis of the ABCD2 added an index in ABCD3: double TIA (TIA attack 2 times or more within 7 days, 2points), the total score nine points; ABCD3I score increased three indicators (double TIA, ipsilateral carotid stenosis, positive DWI), a total of eight items: age 60 years or more (1 point), blood pressure >140/90 MMHG (1 point), clinical symptoms (words damaged 1 points; partial side limb weakness 2 points), duration of symptoms (10-59 minutes 1point; 2 minutes and 60 minutes or higher), diabetes (1 point), double TIA, carotid stenosis and positive DWI (2 points), and all score of 13 points.…”
Section: Abcd3 and Abcd3i Scorementioning
confidence: 99%